Effects of self-help mindfulness-based psychoeducational program for caregiver wellbeing of disabled elderly - S. Ramasamy, Mohan (2019)
In recent years, the number of informal caregivers provided unpaid support for disabled dependent elderly at home has increased and is likely to continue to increase due to aging of the Malaysian population. The provision of this support, however, comes at a cost to the caregivers’ health and wellbeing. Efforts have been made to alleviate these consequences through various forms of psycho-educational programs aimed to enable the caregivers to meet these demands. The reported success of these psycho-educational programs is varied in regards to their effectiveness; an argument supported by literature review papers on the subject that questions the methodologies and evaluations of these programs. There is a need to explore the ways to decrease caregivers’ perceived stress and to promote positive reappraisal outcomes like mindfulness, self-compassion and satisfaction with life of informal caregivers by means of a robust design and evaluation. This thesis reports a study, the aim of which is to provide information about how to reduce the negative effects of the carer role whilst enhancing the positive effects using a self-help mindfulness-based psycho-educational program developed using lived experience. The self-help mindfulness-based psycho-educational program was developed and piloted with those caring for a disabled dependent elderly. This was achieved in three stages: (i) qualitative interviews with caregivers to explore and understand the role, (ii) developing the intervention program informed by qualitative findings, and finally by (iii) randomized evaluation of the intervention program. Effectiveness of the intervention program was determined using positive reappraisal outcomes like mindfulness, self compassion and satisfaction with life, the results of which were compared to a control group who did not take part in the intervention program. The results indicated that self-compassion, satisfaction with life and mindfulness significantly higher following the mindfulness-based psycho- education training program as an intervention for the treatment group compared to the control group. There was also significant difference between the groups in caregiver role strain. This study demonstrates that a mindfulness-based psychoeducation training program may be a viable option to facilitate caregivers’ wellbeing. This mindfulness-based psycho-education training program requires less financial and time resources compared to other typical stress reduction programs and is potentially more agreeable to caregivers’ schedules. This study recommended that the future research should include an active control condition and explore whether similar findings can be extended to clinical populations. The training effects were also persistent after three months from the last intervention session. In contributing to existing research, the use of hermeneutic phenomenology provided new insight in to the experiences of those providing care. The outcome of the intervention pilot shows positive potential for the use of interventions beyond psychoeducation alone and the use of a self-care approach.